Aeroelastic modeling to study the wind-induced response of a self-supported lattice tower. (15th October 2021) - Azzi, Ziad; Elawady, Amal; Irwin, Peter; Chowdhury, Arindam Gan; Shdid, Caesar Abi
Highlights: Aeroelastic modeling of lattice transmission tower. Experimental along- and across-wind aerodynamic damping are obtained. Theoretical buffeting response is compared with experimental recorded values. Incorporation of change in turbulence intensity improves predicted buffeting response. Obtained drag coefficients well in agreement with standards. Resonant contribution in total response still not fully understood by researchers. Abstract: The results from a 1:50 scale aeroelastic model of a self-supported steel lattice tower subjected to simulated hurricane winds are presented. The lattice tower considered is a typical structure that is used as part of a tower-insulator-conductor system for electrical transmission infrastructure. The aeroelastic tests were conducted at the NSF Wall of Wind Experimental Facility (WOW EF) at the Florida International University (FIU). The tower was tested at various wind speeds ranging from 50 m/s to 92 m/s (equivalent full-scale speeds) for varying wind directions. Two system identification (SID) techniques were utilized to evaluate along-wind aerodynamic damping and compare with theoretical estimates. The SID techniques were also utilized to evaluate crosswind aerodynamic damping. A buffeting analysis was conducted to estimate the response of the tower and compare it to measured values at the WOW. Drag and moment coefficients were calculated from the measured responses, and the dynamic amplification factors (DAF) as well as gust effect factors were computed. The analysis required consideration of the variation of the turbulence intensity along the height of the tower in the buffeting analytical equations. The drag coefficients are shown to agree with values proposed in the current standards. However, there might be a need to introduce base moment coefficients in lattice tower design. The resonance contribution is shown to reach a maximum of 18% of the peak response of the tower.